Dinamika Perubahan Sosial Budaya pada Tradisi Makepung di Kabupaten Jembrana - I Made Bawadi Adistanaya; I Wayan Mudana; Irwan Nur (CV Global Research Publication, 2026)
Makepung is a tradition in Jembrana Regency practiced by the local community as an expression of gratitude for their rice harvest; however, as time has passed, this tradition has undergone significant changes. This study aims to identify the sociocultural changes occurring in Makepung, the causes of these changes, and the impacts resulting from them. This study employs a qualitative method with an ethnographic approach. Data were collected through participant observation, unstructured in-depth interviews, and document analysis. The findings reveal that the Makepung tradition has undergone significant socio-cultural changes across six aspects: the form of implementation (from spontaneous to structured), social function (from farmers’ entertainment to regional identity and tourism promotion), meaning and values (from simplicity and gratitude to competition and prestige), participants (from a homogeneous agrarian group to a heterogeneous multi-stakeholder group), venue (from rice fields to an official circuit), and accessories (from simple to luxurious). These changes did not occur overnight but resulted from several factors, ranging from modernization and government intervention to a gradual evolution that went largely unnoticed. These changes have had a general impact, such that the public now views Makepung as a cohesive and uniform cultural entity. Additionally, these changes have had a differential impact: due to the interactions and agreements among Makepung practitioners, this has led to numerous changes resulting from mutual consensus.